The Role of the Community in Preserving the Jamasan Pusaka Bende Tradition in Bumijawa Village, Tegal Regency: A Study from a Cultural Anthropological Perspective - Fifit Asani Putri; Asep Ginanjar (Historia, 2027)
This study aims to analyze the role of the community in preserving the Jamasan Heirloom Bende Tradition in Bumijawa Village, Tegal Regency, from a cultural anthropological perspective. The Jamasan tradition is a ritual for cleansing heirlooms, rich in historical, symbolic, social, and spiritual values, and is part of the community's collective identity. Amidst the current of modernization, this tradition faces challenges in the form of changing participation patterns and shifting views of the younger generation towards local culture. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews and documentation. Informants included caretakers, young cultural activists, and the Head of Bumijawa Village. Data analysis used the interactive model of Miles and Huberman through the stages of data reduction, data presentation, and drawing conclusions. The results show that this tradition is interpreted as an expression of gratitude, a symbol of self-purification, and a means of strengthening social solidarity and community identity. Its preservation is supported by the active role of residents and the village government on an ongoing basis.